PERLINDUNGAN HUKUM TERHADAP PEMBELI BERITIKAD BAIK ATAS PEMBELIAN RUKO BERDASARKAN PERJANJIAN PENGIKATAN JUAL BELI (PPJB) LUNAS DALAM HAL PENJUAL WANPRESTASI - Subowo, Raden; Sudarto, Sudarto (LITERATUS, 2024)
The purpose of this research is to analyze "LEGAL PROTECTION FOR GOOD-FAITH BUYERS IN THE PURCHASE OF SHOPHOUSES BASED ON FULLY PAID SALE AND PURCHASE BINDING AGREEMENT (PPJB) IN THE EVENT OF SELLER'S DEFAULT." This paper is motivated by the questions of how good-faith buyers are regulated in the sale and purchase of shophouses based on the Sale and Purchase Binding Agreement (PPJB) in Indonesian civil law, and how legal protection is afforded to good-faith buyers in the purchase of shophouses under a fully paid PPJB in the event of the seller's default, according to Indonesian judicial practice. The writing method is descriptive-analytical, and the research method uses a Normative Legal Research method, or literature research, which is oriented towards data sourced from literature and similar references related to the preparation of this academic paper. This academic work aims to explore the legal strength and protection offered by the PPJB as a preliminary agreement leading to the Deed of Sale and Purchase (AJB).